Metformin Corrects Glucose Metabolism Reprogramming and NLRP3 Inflammasome-Induced Pyroptosis via Inhibiting the TLR4/NF-κB/PFKFB3 Signaling in Trophoblasts: Implication for a Potential Therapy of Preeclampsia. (11th November 2021) - Zhang, Yang; Liu, Weifang; Zhong, Yanqi; Li, Qi; Wu, Mengying; Yang, Liu; Liu, Xiaoxia; Zou, Li
Abstract : NOD-like receptor family, pyrin domain-containing protein 3 (NLRP3) inflammasome-mediated pyroptosis is a crucial event in the preeclamptic pathogenesis, tightly linked with the uteroplacental TLR4/NF- κ B signaling. Trophoblastic glycometabolism reprogramming has now been noticed in the preeclampsia pathogenesis, plausibly modulated by the TLR4/NF- κ B signaling as well. Intriguingly, cellular pyroptosis and metabolic phenotypes may be inextricably linked and interacted. Metformin (MET), a widely accepted NF- κ B signaling inhibitor, may have therapeutic potential in preeclampsia while the underlying mechanisms remain unclear. Herein, we investigated the role of MET on trophoblastic pyroptosis and its relevant metabolism reprogramming. The safety of pharmacologic MET concentration to trophoblasts was verified at first, which had no adverse effects on trophoblastic viability. Pharmacological MET concentration suppressed NLRP3 inflammasome-induced pyroptosis partly through inhibiting the TLR4/NF- κ B signaling in preeclamptic trophoblast models induced via low-dose lipopolysaccharide. Besides, MET corrected the glycometabolic reprogramming and oxidative stress partly via suppressing the TLR4/NF- κ B signaling and blocking transcription factor NF- κ B1 binding on the promoter PFKFB3, a potent glycolytic accelerator. Furthermore, PFKFB3 can also enhance the NF- κ B signaling, reduce NLRP3 ubiquitination, and aggravate pyroptosis. However, MET suppressed pyroptosis partly via inhibiting PFKFB3 as well. These results provided that the TLR4/NF- κ B/PFKFB3 pathway may be a novel link between metabolism reprogramming and NLRP3 inflammasome-induced pyroptosis in trophoblasts. Further, MET alleviates the NLRP3 inflammasome-induced pyroptosis, which partly relies on the regulation of TLR4/NF- κ B/PFKFB3-dependent glycometabolism reprogramming and redox disorders. Hence, our results provide novel insights into the pathogenesis of preeclampsia and propose MET as a potential therapy.